Features of Hotel Marketing Research - Azimova Makhfuza Rashidovna (Indonesian Journal of Innovation Studies, 2022)
The article discusses the features of marketing research in the hotel services market to determine the needs of various consumer groups since the products and constantly developing activities of hotel enterprises are built thanks to a strong foundation in the form of well-conducted market segmentation. The article reveals the main criteria for determining the market segment. Among the main segmentation criteria in the hotel services market, there are geographic, behavioral, demographic, psychographic, depending on the level of guest loyalty, the age of consumer segments and customer expectations of the level of quality of hotel services, also on the purpose of the guest's arrival and on the status of hotel attendance. Methods for determining target segments are the concentrated "ant method", the dispersed "dragonfly method" and the method of cluster analysis and groupings.